Isolasi Bakteri Pendegradasi Minyak Solar Dari Perairan Teluk Pare-Pare - Hasyimuddin A; M Natsir Djide; M Farid Samawi (Biogenesis: Jurnal Ilmiah Biologi, 2016)
This study aims to acquire the diesel oil degrading microbia in Pare-Pare port. This study was conducted at the Laboratory of Microbiology, Department of Biology, Faculty of Science and Technology, UIN Alauddin Makassar. The method is descriptive exploratory study. The data was analyzed by tables and graphs. The results showed that three isolates of bacteria isolated from the Pare-Pare Bay that can degrade diesel oil as Bacillus sp., Psedomonas aeruginosa, and Alkaligenes feacalis. P. aeruginosa is the best bacteria in degrading diesel oil.